ROLE OF CENTRAL JAVA POLICE KESBANGPOL AGENCY IN PREVENTING AND COMMANDING EXTREMISM THROUGH DIGITAL CONTENT - Adam Mursyid; Lalu Satria Utama; M Nur Shobah; Pitaloka Dyah P; Nabila Risqi A (Sekolah Tinggi Pariwisata Mataram, 2022)
This research was carried out because of the problems of acts of terrorism and radicalism in Indonesia, especially in the Central Java Province, although there were no acts of terror but there were indications of the spread of radicalism that occurred in the community. In order to discuss this problem, the researcher wants to raise the role of the National Unity and Political Agency (Kesbangpol) of Central Java Province in preventing and overcoming extremism through digital content in this study. This study uses a descriptive method and a qualitative approach. From the results of the study, researchers found the fact that the Central Java Provincial Kesbangpol Agency succeeded in preventing and overcoming extremism through digital content uploaded on platforms such as Instagram, YouTube, Facebook, and Twitter. Based on the discussion presented, it can be concluded that the efforts to prevent and overcome extremism have been carried out properly and correctly. It is proven through the YouTube channel that the Central Java Provincial Kesbangpol Agency has uploaded and posted posters on the Instagram, YouTube, Facebook platforms related to efforts to prevent and overcome extremism in Central Java Province.